Roller girl ebook (newbery honor award winner). - Jamieson, Victoria (2015)
The Newbery Honor Award Winner and New York Times bestseller Roller Girl is a heartwarming graphic novel about friendship and surviving junior high through the power of roller derby—perfect for fans of Raina Telgemeier's  Smile !  For most of her twelve years, Astrid has done everything with her best friend Nicole. But after Astrid falls in love with roller derby and signs up for derby camp, Nicole decides to go to dance camp instead. And so begins the most difficult summer of Astrid's life as she struggles to keep up with the older girls at camp, hang on to the friend she feels slipping away, and cautiously embark on a new friendship. As the end of summer nears and her first roller derby bout (and junior high!) draws closer, Astrid realizes that maybe she is strong enough to handle the bout, a lost friendship, and middle school… in short, strong enough to be a roller girl. In this graphic novel debut that earned a Newbery Honor and five starred reviews, real-life derby girl Victoria Jamieson has created an inspiring coming-of-age story about friendship, perseverance, and girl power!